The effect of the determinants of the financing structure on financial leverage: Applied study of a sample of companies listed in the Iraq Stock Exchange). - Khudair Jawan, Haider; Ahmed Fares, Ali (Iraqi Journal for Administrative Sciences, 2024)
The research seeks to test the impact and contribution of the determinants of the financing structure represented by (company size, age, tangibility of assets, profitability, liquidity, growth opportunities and tax shield) in the financial leverage of a sample of Iraqi industrial companies listed on the Iraq Stock Exchange (ISX). The problem of the study was represented in the difficulties facing Iraqi companies in exploiting the determinants of the financing structure to reduce financing costs by determining the appropriate financial leverage and choosing the appropriate financing mixture. The research was conducted in the industrial sector of the above market out of a total of 25 representing the research community, while the sample consists of 5 companies, over a 14-year period extending from 2005 to 2018. The researchers used well-known financial methods to extract the value of the company's size and life, in addition to the tangibility of assets and opportunities for growth, as well as the rate of return on assets, the ratio of trading and tax exemption, and finally the researchers used the financial leverage represented by the ratio of liabilities to assets. The researchers relied for the purpose of testing the effect of the independent variables on the dependent variable on multiple regression. The results showed that the determinants of the financing structure for all companies had a significant effect on the financial leverage.